2015
DOI: 10.1093/eurpub/ckv093
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of parenting: findings from a UK longitudinal study

Abstract: Background: The quality of parenting is associated with a wide range of child and adult outcomes, and there is evidence to suggest that some aspects of parenting show patterns of intergenerational transmission. This study aimed to determine whether such intergenerational transmission occurs in mothers and fathers in a UK birth cohort. Methods: The study sample consisted of 146 mothers and 146 fathers who were recruited from maternity wards in England and followed up for 24 months [‘Generation 2’ (G2)]. Percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 37 publications
(49 reference statements)
5
64
0
13
Order By: Relevance
“…Moreover, specific positive parenting behaviors such as warmth, responsiveness, and encouragement have transgenerational tendencies (Schofield, Conger, & Neppl, 2014). In a longitudinal study, Madden et al (2015) reported that parenting behaviors such as parental control, responsiveness, and decreased engagement transmitted across generations. Clearly, children learn how to communicate as a parent based, in part, on observing their parent's behaviors.…”
Section: How Communication Orientations Transmit Across Generationsmentioning
confidence: 99%
“…Moreover, specific positive parenting behaviors such as warmth, responsiveness, and encouragement have transgenerational tendencies (Schofield, Conger, & Neppl, 2014). In a longitudinal study, Madden et al (2015) reported that parenting behaviors such as parental control, responsiveness, and decreased engagement transmitted across generations. Clearly, children learn how to communicate as a parent based, in part, on observing their parent's behaviors.…”
Section: How Communication Orientations Transmit Across Generationsmentioning
confidence: 99%
“…This may help explain why the teen's mother is often identified as an important source of support for teen mothers and their children (Beers & Hollo, ; Hudson et al, ; Spieker & Bensley, ). Evidence continues to emerge of intergenerational transmission of parenting behaviors and quality; most compelling is the influence of grandmothers (Kretchmar & Jacobvitz, ; Madden et al, ). Greater social support and more positive grandmother relationships have been associated with greater parenting competence and higher levels of nurturing behaviors among teen mothers (Oberlander, Black, & Starr, ; Sellers, Black, Boris, Oberlander, & Myers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, un estudio transversal aplicado en niños de Rumania puntualiza que el nivel educativo y la historia personal de los padres influyen en el tipo de relaciones que estos establecen con sus hijos (69), mientras que otro estudio longitudinal sugiere patrones de transmisión intergeneracional, ya que de acuerdo con la evaluación la paternidad positiva o negativa era transmitida por las conductas de paternidad de las abuelas (70). En otro estudio, donde se examinó una muestra de participantes de los suburbios de alto riesgo en Seattle, con edades entre 10 y 27 años, se estableció que existe relación entre la actual crianza autoritaria e inflexible percibida por los encuestados y los comportamientos antisociales desarrollados por los padres desde su infancia-adolescencia hasta la vida adulta (71).…”
Section: Discussionunclassified